2021
DOI: 10.5897/ajb2021.17388
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-horizontal subsurface flow hybrid constructed wetlands for municipal wastewater treatment in developing countries: A review

Abstract: The use of low-cost on-site wastewater treatment technologies, including constructed wetlands (CWs), is wide spread. Despite the purported high performance of vertical-horizontal subsurface flow (V-H SSF) hybrid CWs, data on implementation and performance in developing countries is scarce. Here, the design, operation and performance of V-H SSF hybrid CWs for treatment of municipal sewage in an effort to encourage and direct future research and assist technology choice were reviewed. Literature reveals that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Another more recent review [ 49 ] has reported removal efficiencies of 84–96% for BOD 5 , 74–95% for COD, 85–99% for TSS, 26–78% for total N, and 19–91% for NH 4 . In this case, all of the values that were obtained in the present study are within these ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another more recent review [ 49 ] has reported removal efficiencies of 84–96% for BOD 5 , 74–95% for COD, 85–99% for TSS, 26–78% for total N, and 19–91% for NH 4 . In this case, all of the values that were obtained in the present study are within these ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, low nutrient removal efficiencies have again been observed, especially for nitrogen compounds. This may be due to the fact that the system design was based on the use of BOD 5 as the parameter of choice and not nitrogen [ 49 ]. The low performance may be correctable by maintaining high levels of oxygenation in the VFCWs [ 33 ] and/or ensuring that the water that is to be treated in the HFCW has sufficient organic matter in order to enable heterotrophic bacteria to carry out the denitrification reaction [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Constructed wetlands are engineered systems that use natural functions of vegetation, soil and microorganisms to treat wastewater (Vymazal, 2008;Parde et al, 2021;Tebitendwa & Cowan 2021). Although used as a sanitation technology, CW is not specifically designed for pathogen removal.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to natural wetlands, a CW acts as a biofilter and either reduces or removes pollutants including suspended solids, organic matter, nutrients (nitrogen and phosphorus) and heavy metals (Gorgoglione & Torretta, 2018). There are essentially two main types of CW: subsurface flow and surface flow CW (Tebitendwa & Cowan 2021) capable of treating a range of different waste streams (Vymazal et al, 2021). The planted vegetation or macrophyte plays an important role in contaminant removal and is potentially a source of renewable energy (Avellána & Gremillion, 2019) while the filter bed, consisting usually of sand and/or gravel, has an equally important role to play (Tebitendwa & Cowan, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation